A stearoyl‐acyl carrier protein desaturase, NbSACPD‐C, is critical for ovule development in Nicotiana benthamiana. (19th September 2014) - Zhang, Jiantao; Li, Jianhui; Garcia‐Ruiz, Hernan; Bates, Philip D.; Mirkov, Theodore Erik; Wang, Xiaofeng
Summary Stearoyl‐acyl carrier protein desaturase (SACPD) activity is essential for production of the major unsaturated fatty acids (UFAs) in plant lipids. We report here the characterization of three SACPD genes from Nicotiana benthamiana, NbSACPD‐A, ‐B, and ‐C. All three genes share high similarity to AtSSI2/FAB2 (Suppressor of Salicylic acid‐Insensitivity2/Fatty Acid Biosynthesis2), the primary SACPD isoform in Arabidopsis. Knocking down the expression of individual or combinations of NbSACPDs by an artificial microRNA approach resulted in significantly reduced accumulation of 18C UFAs and elevated levels of 18:0‐FA (Fatty acids) in leaves, indicating that all three genes participated in fatty acid desaturation. The triple knockdown (KD) plants displayed severe growth phenotypes, including spontaneous cell death and dwarfing. While no vegetative morphologic abnormality was observed in NbSACPD‐A, ‐B, or ‐C KD plants, strikingly, NbSACPD‐C KD plants produced small fruits with aborted ovules. Reciprocal crosses with wild‐type and NbSACPD‐C KD plants revealed that knocking down NbSACPD‐C expression caused female, but not male, sterility. Furthermore, arrested ovule development and significantly altered lipid composition in ovaries were observed in NbSACPD‐C KD plants, consistent with the predominant NbSACPD‐C expression in ovules. The ovule development defect was fully complemented by coexpressing an amiRNA‐resistant NbSACPD‐C variant in the NbSACPD‐C KD background, further supporting a specific requirement for NbSACPD‐C in female fertility. Our results thus indicated that NbSACPD‐C plays a critical role maintaining membrane lipid composition in ovule development for female fertility in N. benthamiana, complementing and extending prior understanding on the well‐demonstrated roles of SACPDs in biotic and abiotic stresses.